Saccade preparation is required for exogenous attention but not endogenous attention or IOR - Smith, D.T.; Schenk, T.; Rorden, C. (Journal of Experimental Psychology: Human Perception and Performance, 2012)
Covert attention is tightly coupled with the control of eye-movements but there is controversy about how tight this coupling is. The Premotor theory of attention proposes that activation of the eye-movement system is necessary to produce shifts of attention. In this study we experimentally prevented healthy participants from planning or executing eye-movements and observed the effect on exogenous attention, Inhibition of Return (IOR) and endogenous attention. The participants experienced a deficit of exogenous attentional facilitation that was specific to locations that were inaccessible by saccade. In contrast their ability to endogenously orient attention was preserved as was IOR. These results show that (a) exogenous attention depends on motor preparation (b) IOR is independent of motor preparation and exogenous attention and (c) endogenous attention is independent of motor preparation. Although these data are consistent with a weak version of the Premotor theory, we believe they can be better explained by a biased competition account of visual attention.
EPrint Processing Status: Full text deposited in DRO
Keywords: Attention; Ophthalmoplegia; Inhibition of Return; Eye-abduction; Premotor; Capture; Cueing; Peripheral; Nasal; Temporal; Oculomotor; IOR; Symbolic; Voluntary; Reflexive.